Pengaruh Brand Equity Terhadap Online Puchase Intention (Studi Kasus Pada Produk Eiger) - Susetya, Ericka Trima; Aquinia, Ajeng (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
There are more and more e-commerce sites in Indonesia are always registering new accounts from day to day on the long list of e-commerce companies present in Indonesia. PT. Eigerindo Multi Produk Industri is a company and brand from Indonesia that produces clothing and outdoor recreation equipment. Brand equity is a consideration for consumers in purchasing decisions because it is able to shape consumer perceptions regarding a product or service that is believed to have higher quality than other products. This research discusses the influence of brand awareness, perceived quality, brand association and brand loyalty on online purchase intention for Eiger products. This research uses a purposive sampling technique with the criteria that respondents have purchased Eiger products, the sample taken was 100 respondents. The results of this research show that all variables are declared valid and reliable so that they can be continued with the multiple linear regression test process. The results of the regression test show that the brand awareness and brand association variables as a whole have no effect on online purchase intention. In other cases, the results of perceived quality and brand loyalty show that the results have a positive effect on online purchase intention.